Degradable polylactic acid plastic film and preparation method thereof

By mixing cellulose nanofibers with ethanol and polyethylene glycol and combining with modified montmorillonite and polylactic acid solution, the problem of poor ductility and thermal stability of polylactic acid films is solved, and its mechanical properties and antibacterial properties are significantly improved. Performance, reduces oxygen and water vapor permeability, and achieves wider applications.

CN119119524AInactive Publication Date: 2024-12-13SHAANXI YICHENG BIOTECHNOLOGY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411218551.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-02
Publication Date
2024-12-13
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The poor ductility, poor thermal stability, poor antibacterial properties and moderate oxygen and water vapor barrier properties of polylactic acid plastic films limit their wide application.

Method used

By mixing cellulose nanofibers with ethanol and homogeneously mixing with polyethylene glycol at room temperature, a gel-like complex was formed and mixed with a solution of modified montmorillonite and polylactic acid in dichloromethane, the modified montex was carried out by modifying montmorillonite and polylactic acid. By plasticizing the soil and improving compatibility, a degradable polylactic acid composite film with improved thermal stability and antibacterial properties was prepared.

Benefits of technology

It significantly improves the thermal stability and antibacterial properties of the polylactic acid composite film, reduces the permeability of oxygen and water vapor, and enhances its mechanical properties and plasticity.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a preparation method of a degradable polylactic acid composite film, and belongs to the technical field of degradable materials.The preparation method comprises the following steps that S1, cellulose nanofibers and ethyl alcohol are mixed and then evenly mixed with polyethylene glycol at the room temperature, and a gelatinous compound is obtained after rotary evaporation; and S2, uniformly mixing the gelatinous compound obtained in the step S1 with a dichloromethane solution of polylactic acid with the concentration of 0.96 mol / L and modified montmorillonite, casting onto culture dish glass, and drying in a drying oven to obtain the degradable polylactic acid composite film. According to the technical scheme, polylactic acid is poor in thermal stability and antibacterial property and moderate in oxygen permeability and water vapor permeability, the thermal stability and the antibacterial property of polylactic acid are remarkably improved by modifying montmorillonite, and the oxygen permeability and the water vapor permeability are remarkably reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of degradable materials, and in particular relates to a degradable polylactic acid plastic film and a preparation method thereof. Background Art

[0002] Polylactic acid (PLA) is derived from biological resources. It is a lactic acid derivative produced from renewable resources such as wheat, straw, corn and sorghum. It is completely biodegradable and has renewable, biodegradable, biocompatible and good mechanical properties. Polylactic acid, also known as polylactide, is favored by researchers and used as a commercial material in various studies. However, PLA has the characteristics of brittleness, slow crystallization, poor thermal stability, poor ductility, and moderate oxygen and water vapor barrier properties, which limit its wide application.

[0003] At present, in order to improve these properties, it is proposed to mix cellulose nanofibers with ethanol and then mix them with polyethylene glycol at room temperature to obtain a gel-like composite, and then mix them with a dichloromethane solution of polylactic acid and modified montmorillonite to obtain a degradable polylactic acid composite film.

[0004] PLA is plasticized by PEG to improve its plasticity. In addition, PEG can be used as a dispersant for cellulose nanofibers, dispersing cellulose nanofibers in PLA and enhancing the mechanical properties of polylactic acid. However, problems such as poor ductility and moderate oxygen and water vapor barrier properties cannot be solved. Summary of the invention

[0005] The object of the present invention is to provide a degradable polylactic acid composite film and a preparation method thereof, wherein cellulose nanofibers are mixed with ethanol and then mixed evenly with polyethylene glycol at room temperature to obtain a gel-like composite, which is then mixed evenly with a dichloromethane solution of polylactic acid and modified montmorillonite to obtain a degradable polylactic acid composite film.

[0006] The technical problem to be solved by the present invention is that the degradable polylactic acid composite film has poor ductility and moderate oxygen and water vapor barrier properties, which limits its wide application. The addition of modified montmorillonite significantly improves thermal stability and antibacterial properties, and significantly reduces oxygen permeability and water vapor permeability.

[0007] The purpose of the present invention can be achieved through the following technical solutions:

[0008] A method for preparing a degradable polylactic acid composite film comprises the following steps:

[0009] S1, mixing cellulose nanofibers with ethanol and then with polyethylene glycol at room temperature, and then rotary evaporating to obtain a gel-like composite;

[0010] S2. Evenly mix the gel-like composite obtained in step S1 with a dichloromethane solution of polylactic acid having a concentration of 0.96 mol / L and modified montmorillonite, cast the mixture on a glass culture dish, and dry it in an oven to obtain a degradable polylactic acid composite film.

[0011] It should be noted that the interlayer of the modified montmorillonite added in the present application contains a large number of hydroxyl groups, so it can help polyethylene glycol to enhance the plasticizing effect of polylactic acid. In addition, the interlayer of the multi-hydroxy structure helps to improve the compatibility of the nanomaterial and the polylactic acid system and helps the dispersion of the nanomaterial.

[0012] Furthermore, in step S1, the mass volume ratio of cellulose nanofibers, ethanol and polyethylene glycol is 1-1.2 g:20-25 mL:10-15 mL.

[0013] Furthermore, in step S1, the rotary evaporation temperature is 80° C. and the time is 24 hours.

[0014] Furthermore, in step S2, the mass volume ratio of the gel-like composite, the dichloromethane solution of polylactic acid and the modified montmorillonite is 5-10 g: 95-100 mL: 5-10 g.

[0015] Furthermore, in step S2, the drying temperature in the oven is 80° C. and the drying time is 24 hours.

[0016] Further, the preparation method of modified montmorillonite is as follows:

[0017] A1. Gradually drop the sodium montmorillonite suspension into the hydrochloric acid solution of octadecyltrimethylammonium bromide, heat the sample in a 90°C water bath for 1 hour, then centrifuge, dry, stand at room temperature, and crush into C18-OMMT fine powder;

[0018] A2. Ultrasonic dispersion of C18-OMMT fine powder and polyphenyl parahydroxybenzoate in chloroform for 2 h to obtain a composite dispersion, followed by stirring in a water bath at 64 °C for 0.5 h and drying in an oven at 55 °C for 48 h to obtain modified montmorillonite.

[0019] It should be noted that sodium montmorillonite has good dispersibility, adsorption, adhesion and other properties. Octadecyl trimethyl ammonium bromide has a strong affinity with sodium montmorillonite. The modification of montmorillonite is to utilize the exchangeability of interlayer ions to introduce octadecyl trimethyl ammonium bromide into the interlayer, thereby improving its activity.

[0020] Furthermore, the suspension of sodium montmorillonite is gradually added dropwise to the hydrochloric acid solution of octadecyltrimethylammonium bromide in a volume ratio of 1.2-1.5:1-1.2.

[0021] Furthermore, in step A2, the volume ratio of C18-OMMT fine powder to polyphenyl parahydroxybenzoate is 2-2.5:1-1.5.

[0022] Furthermore, the particle size of the C18-OMMT fine powder is 18 μm to 74 μm.

[0023] Beneficial effects of the present invention:

[0024] (1) In the technical solution of the present invention, the plasticity of polylactic acid can be improved by reacting fiber nanofibers with polyethylene glycol. In addition, polyethylene glycol can be used as a dispersant for fiber nanofibers to enhance the mechanical properties of polylactic acid.

[0025] (2) In the technical solution of the present invention, modified montmorillonite is used as an additive to participate in the reaction, which can help polyethylene glycol to enhance the plasticization of polylactic acid. In addition, it can also help to improve the compatibility of nanomaterials and polylactic acid systems and help disperse nanomaterials.

[0026] (3) In the technical solution of the present invention, the thermal stability and antibacterial properties of polylactic acid are poor, and the oxygen permeability and water vapor permeability are moderate. By modifying montmorillonite, the thermal stability and antibacterial properties of polylactic acid are significantly improved, and the oxygen permeability and water vapor permeability are significantly reduced. DETAILED DESCRIPTION

[0027] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] In the present invention, the specific preparation process of modified montmorillonite is as follows:

[0029] a. 1.35 mL of 0.05 g / mL octadecyltrimethylammonium bromide (STAB) hydrochloric acid solution was gradually added to 1.1 mL of 0.01 g / mL sodium montmorillonite (NMMT) aqueous suspension. The sample was heated in a water bath for 1 hour, then centrifuged, dried, allowed to stand at room temperature, and crushed into a fine powder called C18-OMMT. The particle size of the fine powder was 18 μm to 74 μm.

[0030] b. Mix 2.3 g of C18-OMMT fine powder with 1.3 g of PHB (polyphenyl parahydroxybenzoate), and disperse them in 50 mL of chloroform by ultrasonication for 2 hours to obtain a composite dispersion, which is then stirred in a water bath at 64°C for 0.5 hours and then dried in an oven at 55°C for 48 hours to obtain modified montmorillonite. The volume ratio of C18-OMMT, PHB, and modified montmorillonite is 2-2.3:1-1.2:5-6.3.

[0031] Example 1

[0032] A method for preparing a degradable polylactic acid film comprises the following steps:

[0033] S1. 1 g of cellulose nanofiber content was dispersed in 20 mL of ethanol using a high-pressure microfluidizer (M-110EH, Microfluidics Inc., USA) through 60 cycles (2000 bar) to obtain a gel-like cellulose nanofiber dispersion, and then the gel-like cellulose nanofiber dispersion was mixed with 10 mL of PEG200 at ambient temperature until the mixture was homogeneous, and the ethanol was removed by using a rotary evaporator at 80 °C, and further dried in a convection oven at 80 °C for 24 h to obtain a gel-like CNFs / PEG;

[0034] S2. Dissolve 5 g of pre-dried PLA particles in 100 g of DCM in an airtight container at room temperature for 24 hours to obtain a PLA solution. Then, mix 95 g of the completely dissolved PLA solution, 5 g of gelatinous CNFs / PEG and 5 g of modified montmorillonite, and homogenize the mixture at a rotation speed of 3000 rpm for 30 minutes using a high-speed homogenizer (Ultraturrax T50 basic, IKA Works (Thailand) Co., Ltd., Thailand), and then cast it onto a Petri dish glass. The Petri dish glass is placed at room temperature for 24 hours (to allow a low evaporation rate of DCM), and then dried in an oven at 40° C. for 24 hours to obtain a composite film.

[0035] Example 2

[0036] A method for preparing a degradable polylactic acid film comprises the following steps:

[0037] S1. 1.1 g of cellulose nanofiber content was dispersed in 22 mL of ethanol. A high-pressure microfluidizer (M-110EH, Microfluidics Co., Ltd., USA) was used to obtain a gel-like cellulose nanofiber dispersion through 60 cycles (2000 bar), and then the gel-like cellulose nanofiber dispersion was mixed with 22 mL of PEG200 at ambient temperature until the mixture was uniform, and the ethanol was removed by using a rotary evaporator at 85 ° C, and further dried in a convection oven at 85 ° C for 24 hours to obtain a gel-like CNFs / PEG;

[0038] S2. 3 g of pre-dried PLA particles were dissolved in 60 g of DCM in an airtight container at room temperature for 24 h to obtain a PLA solution. Then, 98 mL of the completely dissolved PLA solution, 7 g of gelatinous CNFs / PEG and 7 g of modified montmorillonite were mixed, and the mixture was homogenized at a rotation speed of 3000 rpm for 30 min using a high-speed homogenizer (Ultraturrax T50 basic, IKA Works (Thailand) Co., Ltd., Thailand), and then cast onto a Petri dish glass, which was left at room temperature for 24 h (to allow a low evaporation rate of DCM), and then dried in an oven at 45 ° C for 24 h to obtain a composite film.

[0039] Example 3

[0040] A method for preparing a degradable polylactic acid film comprises the following steps:

[0041] S1. 1.2 g of cellulose nanofiber content was dispersed in 25 mL of ethanol. A high-pressure microfluidizer (M-110EH, Microfluidics Co., Ltd., USA) was used to obtain a gel-like cellulose nanofiber dispersion through 60 cycles (2000 bar), and then the gel-like cellulose nanofiber dispersion was mixed with 12 mL of PEG200 at ambient temperature until the mixture was uniform, and the ethanol was removed by using a rotary evaporator at 80 ° C, and further dried in a convection oven at 80 ° C for 24 hours to obtain a gel-like CNFs / PEG;

[0042] S2. 6 g of pre-dried PLA particles were dissolved in 100 g of DCM in an airtight container at room temperature for 24 hours to obtain a PLA solution. Then, 100 mL of the completely dissolved PLA solution, 10 g of gelatinous CNFs / PEG and 10 g of modified montmorillonite were mixed, and the mixture was homogenized at a rotation speed of 3000 rpm for 30 minutes using a high-speed homogenizer (Ultraturrax T50basic, IKA Works (Thailand) Co., Ltd., Thailand), and then cast onto a Petri dish glass, which was placed at room temperature for 24 hours (to allow a low evaporation rate of DCM), and then dried in an oven at 40° C. for 24 hours to obtain a composite film.

[0043] Comparative Example 1

[0044] Compared with Example 1, no modified montmorillonite was added in Comparative Example 1, and other steps and raw materials were the same as those in Example 1.

[0045] Comparative Example 2

[0046] Compared with Example 1, unmodified montmorillonite was added in Comparative Example 2, and the other steps and raw materials were the same as those in Example 1.

[0047] The performance of the degradable polylactic acid films of Examples 1-3 and Comparative Examples 1-2 is tested, and the results are shown in Table 1.

[0048] Performance Test:

[0049] (1) Tensile strength: Through uniaxial tension, the farthest length of the specimen is 5 mm and the tensile length is the maximum limit.

[0050] (2) Elongation at break: Elongation at break can indicate the elongation deformation capacity of the degradable polylactic acid film when it is subjected to the maximum load. e = (La-L0) / L0, where e is the elongation at break, L0 is the original length of the sample, and La is the length of the sample when it is broken.

[0051] Table 1

[0052] project <![CDATA[Tensile strength / N / mm 2 > Elongation at break / % Example 1 95.56 229.60 Example 2 90.28 190.04 Example 3 91.49 164.40 Comparative Example 1 75.1 42.40 Comparative Example 2 78.2 73.60

[0053] It can be seen from the data of Examples 1-3 in Table 1 that the addition of modified montmorillonite makes the degradable polylactic acid film have stronger plasticity.

[0054] From the data of comparison example 1 and comparative example 1, it can be seen that no modified montmorillonite was added in comparative example 1, resulting in poor plasticity of the degradable polylactic acid film, poor dispersibility of the fiber nanofibers, and difficulty in mixing with PEG, resulting in decreased plasticity.

[0055] By comparing the data of Example 1 and Example 2, it can be seen that in Example 1, unmodified montmorillonite is added to Example 2. The unmodified montmorillonite will cause weak interface bonding and serious agglomeration during the blending process. However, the interlayer of the modified montmorillonite has a large number of hydroxyl groups, which is beneficial to improve the compatibility of the fiber nanofibers and polylactic acid, and at the same time helps PEG to enhance the plasticization of polylactic acid.

[0056] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a degradable polylactic acid composite film, characterized in that: The following steps are involved: S1, mixing cellulose nanofibers with ethanol and then with polyethylene glycol at room temperature, and then rotary evaporating to obtain a gel-like composite; S2. Evenly mix the gel-like composite obtained in step S1 with a dichloromethane solution of polylactic acid having a concentration of 0.96 mol / L and modified montmorillonite, cast the mixture on a glass culture dish, and dry it in an oven to obtain a degradable polylactic acid composite film.

2. The method for preparing a degradable polylactic acid composite film according to claim 1, characterized in that: In step S1, the mass volume ratio of cellulose nanofibers, ethanol and polyethylene glycol is 1-1.2 g:20-25 mL:10-15 mL.

3. The method for preparing a degradable polylactic acid composite film according to claim 1, characterized in that: In step S1, the rotary evaporation temperature is 80° C. and the time is 24 h.

4. The method for preparing a degradable polylactic acid composite film according to claim 1, characterized in that: The mass volume ratio of the gel-like composite, the dichloromethane solution of polylactic acid and the modified montmorillonite is 5-10g:95-100mL:5-10g.

5. The method for preparing a degradable polylactic acid composite film according to claim 1, characterized in that: The drying temperature in the oven in step S2 is 80° C. and the drying time is 24 h.

6. The method for preparing a degradable polylactic acid composite film according to claim 1 or 5, characterized in that: The preparation method of modified montmorillonite is as follows: A1. Gradually drop the sodium montmorillonite suspension into the hydrochloric acid solution of octadecyltrimethylammonium bromide, heat the sample in a 90°C water bath for 1 hour, then centrifuge, dry, stand at room temperature, and crush into C18-OMMT fine powder; A2. Ultrasonic dispersion of C18-OMMT fine powder and polyphenyl parahydroxybenzoate in chloroform for 2 h to obtain a composite dispersion, followed by stirring in a water bath at 64 °C for 0.5 h and drying in an oven at 55 °C for 48 h to obtain modified montmorillonite.

7. The method for preparing a degradable polylactic acid composite film according to claim 6, characterized in that: The suspension of sodium montmorillonite is gradually added dropwise to the hydrochloric acid solution of octadecyltrimethylammonium bromide in a volume ratio of 1.2-1.5:1-1.

2.

8. The method for preparing a degradable polylactic acid composite film according to claim 6, characterized in that: In step A2, the volume ratio of C18-OMMT fine powder to polyphenyl parahydroxybenzoate is 2-2.5:1-1.

5.

9. The method for preparing modified montmorillonite according to claim 6, characterized in that: The particle size of C18-OMMT fine powder is 18 μm to 74 μm. A degradable polylactic acid composite film obtained by the preparation method according to any one of claims 1 to 9.

Citation Information

Cited By

  • Degradable mask cloth and preparation method thereof

    CN119837768A